Differential diagnosis of late‐type reactions to injected local anaesthetics: Inflammation at the injection site is the only indicator of allergic hypersensitivity. (11th October 2018) - Trautmann, Axel; Stoevesandt, Johanna
Abstract : Background: Anaphylaxis‐like reactions developing within a few minutes are the most frequent complications of subcutaneous or submucosal injections of local anaesthetics (LAs), and topically applied LAs are potential contact allergens. In addition, injected LAs have been reported to induce delayed reactions, including local inflammation at the injection site, and various general symptoms. Objectives: To assess the frequency and symptoms of late‐type hypersensitivity occurring several hours after LA injections. Methods: We retrospectively evaluated clinical data and test results from all patients referred to our allergy clinic in a period of 20 years for diagnostic work‐up of LA‐associated late‐type reactions. Results: Of 202 patients reporting symptoms with onset at least 1 hour after LA injection, 40 had cutaneous inflammation confined to the injection site, and 162 reported various systemic symptoms. LA hypersensitivity could be excluded in all patients with systemic complaints by means of skin testing and subsequent subcutaneous provocation. In 8 of the 40 patients (20%) with local inflammatory reactions, late‐type allergic LA hypersensitivity was confirmed. Conclusions: Late‐type LA allergy commonly causes inflammatory skin reactions confined to the injection site. Conversely, LAs are highly unlikely to trigger delayed systemic symptoms such as urticarial or exanthematous skin eruptions.